Financial indicators of the company from electrical engineering industry: the case study of Tesla, inc. - Jenčová, Sylvia; Vasanicova, Petra; Litavcová, Eva (Serbian Journal of Management, 2019)
Enterprise performance assessment and analysis is a key part of business management. The quantification of the impact of the relevant analytical indicators, which determining the overall profitability of the business entity, is the basis for an appropriate interpretation of the financial indicators. The aim of this paper is to analyze the financial indicators of the Tesla, Inc. that is the company operating in the electrical engineering industry in Slovakia, during the period 2012-2016. The absolute and the relative impacts of the analytical factors on the economic criterion of efficiency, were compared by using the methods of quantifying the influence of determining factors. In addition, the development of company’s indicators with indicators for the whole Slovak electrical engineering industry were compared. Company’s data were obtained from the Register of Financial Statements of the Slovak Republic; data of the whole industry were obtained from the CRIBIS database. This case study provides information for the financial management of the analyzed company.